Intertextuality in Ukrainian-Language Newspaper Discourse During the Wartime Period: Cognitive-Pragmatic Dimension - Maslova, Yuliia (Slavistica Vilnensis, 2025)
The article investigates intertextuality in the journalistic discourse of Ukrainian-language wartime newspapers as a cognitive-pragmatic marker that embeds precedent texts and cultural codes in the construction of new narratives. The study explores the attractive, persuasive, and axiological functions of intertextuality that enhance its communicative impact on the recipient. It highlights the role of strategically selected intertextual elements in the cognitive modelling of reality, the construction of collective memory, and the ideological orientation of newspaper discourse. The pragmatic mechanisms for employing precedent phenomena, allusions, reminiscences, and quotations are analysed as tools for integrating new content into a broader cultural and historical context. The findings establish that intertextuality performs the meaning-generating and cognitive-axiological functions by activating collective mental models and emotionally evaluative structures within media discourse. Intertextual interaction promotes semantic cohesion and cognitive integration, ensuring textual attraction, argumentativity, and pragmatic impact. Ultimately, intertextuality in wartime newspaper discourse functions as a cognitive mediator, securing pragmatic relevance and discursive cohesion.